PLACES IN HISTORY OF THE HONDUREAN AND THE PARAGUAYAN EDUCATION - García Laínez, Andrés Eduardo; Elías, Rodolfo; Morales-Ulloa, Ricardo (Historia y Memoria de la Educación, 2024)
Is there a historiographic production of education in Honduras and Paraguay? What are your dissemination vehicles? What intentions, policies and contexts do they obey? What kind of history of education is produced? These are some of the questions that this article tries to answer by describing the places occupied by the discursive constructions of the history of Honduran and Paraguayan education in works from the field of social sciences, specifically sociology, linguistics and history, highlighting the works that are from the field of educational history. The result of this exercise gave visibility not only to the recurrences of this type of historical construction of education in both countries, but also to the materiality of the objects consulted linked to their historical-political context, thus offering elements of intelligibility to understand the scattered field production in such countries. The article ends by showing the recent efforts for the constitution of the field of the history of education as well as the importance of investing in the historiographic study of academic articles and memories of national and international events, either from the academic-official path, as it is the case of the Directorate of History and Heritage (DIHIPA), a body of the Honduran Ministry of Education; or the Academic - University path, as is the case of Paraguay with the formation of its Society for the History of Paraguayan Education that will organize the XV Ibero-American Congress of the History of Education (CIHELA) in 2023.